Gus Dur's Thought about Accommodation of Islamic Law and Culture - Suardi Kaco H; Busrah Busrah (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2022)
This paper is a study of Gus Dur's thoughts on the accommodation of Islamic law and culture. The research method used is the library research method by analyzing the data qualitatively. In this study it was found that Gus Dur is a contemporary Islamic law thinker whose Islamic legal thought is accommodating to culture. In his thinking, Gus Dur used ushul fiqh, qaidah fiqh, and maqashid syariah in responding to personal problems that occurred in Indonesia. One of the cases that Gus Dur responded to within the cultural framework was zakat law, Islamic marriage law, and islamic inheritance law. In these cases, in Gus Dur's view, the law may be applied with cultural instruments, in this case is customs (adat).Tulisan ini meneliti pemikiran Gus Dur tentang akomodasi hukum Islam dan kebudayaan. Metodo penelitian yang digunakan, yakni metode penelitian kepustakaan (library research) dengan menganalisis data secara kualitatif. Dalam penelitian ini ditemukan bahwa Gus Dur adalah pemikir hukum Islam kontemporer yang pemikiran hukum Islamnya akomodatif terhadap kebudayaan. Gus Dur dalam pemikirannya banyak menggunakan ushul fiqh, qaidah fiqh, dan maqashid Syariah dalam merespon persoalan-persoalan hukum yang terjadi di Indonesia. Salah satu kasus yang direspon oleh Gus Dur dalam kerangka kebudayaan adalah zakat, perkawinan, dan kewarisan. Kasus-kasus ini, dalam pandangan Gus Dur, hukumnya boleh diaplikasikan dengan perangkat kebudayaan, dalam hal ini adalah adat.